Lemongrass Powder in Bio-Bs Effervescent Formulation of Lombok Island Local Isolate on Viability and Amount of Bacillus Sphaericus Toxin Crystal Protein for Control of Anopheles sp. Larvae - Yunan Jiwintarum; Zainal Fikri; Maruni Wiwin Diarti; Rabi'unnisa Sulaimah (Jurnal Analis Medika Biosains (JAMBS), 2023)
Bio Formula – BS effervescent (Bio- Bacillus sphaericus) is an Effervescent powder-shaped formula that is easy to use by the public. Lombok's local effervescent bio-BS isolated formula has a weakness in terms of smell. The results from the literature search that fragrant lemongrass has a distinctive smell and can kill Aedes aeygpti, but scientific data has not been obtained about the ability of fragrant lemongrass to kill Anopheles Sp in the form of larvae and mosquitoes. The study aimed to find out the effect of the combination formulation of Bio-BS Effervescent local isolate Lombok Island with the addition of lemongrass powder for viability and the amount of toxin crystal protein Bacillus sphaericus. This research method is exploratory and experimental in the laboratory with the design of Post Test Only Control Group Design. The study used six treatment formulations. Samples of Anopheles sp larvae research in Batu Layar lagoon, West Lombok regency and pelur lagoon in Peringgesela, East Lombok regency and from the results of colonization of larvae. The independent Variable is a combination formulation of Bio-BS Effervescent isolated locally from Lombok Island with the addition of fragrant lemongrass powder. The dependent variable is the mortality of Larvae Anophels Sp, Viability of B. Sphaericus, and Amount of Toxin Protein Production of B. Sphaericus. The larvae death rate, the concentration of cells/endospores, and the number of repeats in each container are then tabulated and analyzed using Probit Analysis with the help of MINITAB 16 software. B. sphaericus viability data and the amount of endospore toxin protein crystal production were descriptively analyzed.